2021
DOI: 10.3389/fimmu.2021.639329
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Adaptive Immune Cells Expressing the Gut Homing Marker α4β7 Integrin Are Decreased in COVID-19

Abstract: BackgroundInfection with the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes a wide range of symptoms including gastrointestinal manifestations, and intestinal epithelial cells are a target of the virus. However, it is unknown how the intestinal immune system contributes to systemic immune responses in coronavirus disease 2019 (COVID-19).MethodsWe characterized peripheral blood lymphocytes from patients with active COVID-19 and convalescent patients as well as healthy controls by flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
5
1
0
Order By: Relevance
“…We also noted a heretofore unreported positive correlation of sMAdCAM levels with CD8+ effector memory T cell counts (Supplementary Figure S4A). This observation concurs with recent data 36 demonstrating lower counts of CD8+ memory T cellsexpressing receptors for sMAdCAM (integrin α4β7) in COVID‐19. Taken together, these results highlight a clear role for altered mucosal homing in the pathogenesis of this disease.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…We also noted a heretofore unreported positive correlation of sMAdCAM levels with CD8+ effector memory T cell counts (Supplementary Figure S4A). This observation concurs with recent data 36 demonstrating lower counts of CD8+ memory T cellsexpressing receptors for sMAdCAM (integrin α4β7) in COVID‐19. Taken together, these results highlight a clear role for altered mucosal homing in the pathogenesis of this disease.…”
Section: Resultssupporting
confidence: 93%
“…We also noted a heretofore unreported positive correlation of sMAd-CAM levels with CD8+ effector memory T cell counts (Supplementary Figure S4A). This observation concurs with recent data 36 reported for severe and ICU patients. 37 In our study we also observed increased plasma LPS levels in hypoxemic individuals compared to seronegative controls (Supplementary Figure S4B) as opposed to our previous work with a cohort of mild COVID-19.…”
Section: Contribution Of Smadcam and Il-6 To Covid-19 Associated Lymp...supporting
confidence: 94%
“…First, we demonstrated that all RBD-specific mBCs, irrespective of the infection/vaccination context, express the β1 or β7 chain of integrins that are critical determinants of mucosal homing imprinting, with a clear dominance of an airway-homing signature. The latter observation is coherent with the study of Müller and colleagues ( 64 ) reporting reduction of α4β7-expressing memory T cells in COVID-19 patients, including those presenting with intestinal symptoms. Because circulating mBCs have been reported to return to the tissue where they were originally generated ( 65 ), our present finding suggested that mucosae of the upper respiratory tract would be prominent sites for induction of mBC not only in the context of infection but also in response to parenteral vaccination.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, we detected a decreased level of ITGA4 (CD49d) mRNA in the severe patients, including those with cardiovascular involvement. This finding is consistent with the reported decrease in the levels of CD49d in adults with severe COVID-19 [ 33 ], suggesting that CD49d might also be a biomarker of worse disease progression in pediatric patients.…”
Section: Discussionsupporting
confidence: 92%